Investigating Users' Continuance Usage Intention Towards Mobile Apps with the Mediating effect of Customer-Brand Engagement - Najjia Ejaz Chaudhry; Waseem Subhani; Muhammad Azeem Naz; Muhammad Umair Nazir; Muhammad Huzaifa Ameer (Journal of Management Practices, Humanities and Social Sciences, 2023)
Mobile commerce is considered a contemporary marketing communication in e-retail. Therefore, we studied how mobile app utility affects customers and continuance usage intention. Moreover, the authors examined customer brand engagement as a mediating factor and privacy risk as a moderator that influences the impact of customer brand engagement on continuance usage intention. Data was collected from the Grocer App grocery service providers on the mobile application. The authors collected data from 445 current customers through "Google Forms." The present study used the structural equation modeling technique to evaluate association among the latent constructs. The study applied SEM and observed that mobile app utility positively affects customers, continuing usage intention through customer brand engagement. Moreover, privacy risk is not considered a significant factor to highlight the significant relationship. Data from online grocery apps representing e-retail branded mobile apps is collected. The study suggests providing more utility and hedonic benefits to compete in a competitive environment. This study is the first to examine continuous usage intention by shedding light on a negative characteristic (privacy risk) in the context of mobile commerce in the presence of customer brand engagement. It does this by drawing on the idea of reasoned action.